2007
DOI: 10.1128/jvi.01877-06
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gamma Interferon and Interleukin-17 Production in Intestinal CD4+T Cells with Protection against Rotavirus Shedding in Mice Intranasally Immunized with VP6 and the Adjuvant LT(R192G)

Abstract: Mucosal immunization of mice with chimeric, Escherichia coli-expressed VP6, the protein that comprises the intermediate capsid layer of the rotavirus particle, together with attenuated E. coli heat-labile toxin LT(R192G) as an adjuvant, reduces fecal shedding of rotavirus antigen by >95% after murine rotavirus challenge, and the only lymphocytes required for protection are CD4 ؉ T cells. Because these cells produce cytokines with antiviral properties, the cytokines whose expression is upregulated in intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 54 publications
0
39
0
3
Order By: Relevance
“…Our study demonstrated a direct correlation between the existence of extralymphoid IFN-γ producing T cells and protection at the site of virus entry (intestine). In studies of mice, intestinal IFN-γ producing CD4+ T cells were suggested to be the only lymphocytes required for protection against rotavirus infection after the mice were immunized with a chimeric VP6 vaccine using attenuated E. coli labile toxin as an adjuvant [15,28,46,47]. Their data and ours collectively emphasize the role of intestinal IFN-γ producing CD4+ T cells as correlates of rotavirus protective immunity, possibly more important than CD8+ T cells.…”
Section: Discussionmentioning
confidence: 55%
“…Our study demonstrated a direct correlation between the existence of extralymphoid IFN-γ producing T cells and protection at the site of virus entry (intestine). In studies of mice, intestinal IFN-γ producing CD4+ T cells were suggested to be the only lymphocytes required for protection against rotavirus infection after the mice were immunized with a chimeric VP6 vaccine using attenuated E. coli labile toxin as an adjuvant [15,28,46,47]. Their data and ours collectively emphasize the role of intestinal IFN-γ producing CD4+ T cells as correlates of rotavirus protective immunity, possibly more important than CD8+ T cells.…”
Section: Discussionmentioning
confidence: 55%
“…Experimental evidence has shown that LT, some mutant LTs, and CT promote Th17 cell development (6,17,35,37,43,53). To assess the contribution of the A subunit to Th17 responses in these animals, we evaluated splenocytes from the OVA-immunized mice for secretion of IL-17 in an antigen restimulation assay.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, antigen-specific adaptive immune responses develop, including IgG1/IgG2a antibodies, mucosal IgA, and mixed Th1/ Th2/Th17/Treg cellular responses, depending upon the intrinsic nature of the coadministered antigen, the type of attenuating mutation to the LT (if any), and the route of immunization (3,6,13,24,37,41,42,53,55). The mechanisms through which LT functions as a mucosal adjuvant are not well understood, and conflicting results have been obtained by different investigators using different preparations of LT, different antigens, and different routes of immunization.…”
mentioning
confidence: 99%
“…Indeed, a recent report observed that CT is able to generate Th17 cells in an IL-6-dependent manner (11), and vaccines containing CT or Escherichia coli heat-labile toxin also induced IL-17 (36)(37)(38)(39), but the mechanisms involved and the role of IL-17 in mediating adjuvant effects (i.e., antibody responses and protection against infection) were not explored. In addition, our data show that a natural biological molecule such as CT induces DCs to secrete a complex mixture of products that are required to act in combination to determine T-cell fate (Fig.…”
Section: Discussionmentioning
confidence: 99%